2022
DOI: 10.1101/2022.09.28.509871
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

svep1 and tie1 genetically interact and affect aspects of facial lymphatic development in a Vegfc-independent manner

Abstract: Multiple factors are required to form functional lymphatic vessels. Here, we uncover an essential role for the secreted protein Svep1 and the transmembrane receptor Tie1 during the development of subpopulations of the zebrafish facial lymphatic network. This specific aspect of the facial network forms independently of Vegfc signalling, which otherwise is the most prominent signalling axis in all other lymphatic beds. Additionally, we find that multiple specific and newly uncovered phenotypic hallmarks of svep1… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 70 publications
0
2
0
Order By: Relevance
“…Tie1 knockout in zebrafish was also shown to cause severe edema ( Carlantoni et al, 2021 ). Recently, Hußmann et al reported that multiple phenotypic traits in the lymphatic and blood vasculature were shared between tie1 -null and svep1/polydom -null zebrafish, and proposed a genetic interaction between svep1/polydom and tie1 ( Hußmann et al, 2022 Preprint ). It should be noted that defects in venous development were observed in the skin of Polydom-deficient mice but were not observed in the cardinal vein or mesenteries ( Morooka et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Tie1 knockout in zebrafish was also shown to cause severe edema ( Carlantoni et al, 2021 ). Recently, Hußmann et al reported that multiple phenotypic traits in the lymphatic and blood vasculature were shared between tie1 -null and svep1/polydom -null zebrafish, and proposed a genetic interaction between svep1/polydom and tie1 ( Hußmann et al, 2022 Preprint ). It should be noted that defects in venous development were observed in the skin of Polydom-deficient mice but were not observed in the cardinal vein or mesenteries ( Morooka et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…In 2006, Yaniv et al (Yaniv et al, 2006) and Küchler et al (Küchler et al, 2006) described the development of lymphatic vascular network in zebrafish embryos using time-lapse imaging of 6 transgenic zebrafish, molecular markers, and morpholino inhibition experiments of the lymphaticspecific VEGFC/VEGFR3 signalling pathway. Since then, many follow-up publications have contributed to our understanding of the lymphatic development in zebrafish (Hogan et al, 2009a;Bussmann et al, 2010;Le Guen et al, 2014;Nicenboim et al, 2015;Koltowska et al, 2015;Jung et al, 2017;Vogrin et al, 2019;Peng et al, 2022;Hußmann et al, 2023;Grimm et al, 2023).…”
Section: The Lymphatic Vascular System Of Fishmentioning
confidence: 99%